Developing Formative Assessment AKM-Based for Recount Text in Reading Skill for Grade X SMA Negeri 1 Pangkalan Susu North Sumatera - Agustina Syafriani; Rahmad Husein; Lidwina Sri Ardiasih (Budapest International Research and Critics University, 2023)
This study aims to 1) explain how the AKM-based recount text formative assessment in class X students' reading skills is developed, 2) describe the validity of AKM-based recount text formative assessment on class X students' reading skills, 3) describe the effectiveness of AKM-based recount text formative assessment in reading skills of class X students. This study uses the Research and Development (R&D) model, consisting of three main stages, namely: preliminary study, development and design of the assessment, validation of the assessment sheet. The results of the study describe the process of developing formative assessment through the stages of literature review, needs analysis, drafting, design, testing, revision, and expert validation. The validation process was carried out on question validation and expert validation, the results of the validation of the questions showed a valid, reliable formative assessment, the level of difficulty was in the